2017
DOI: 10.2135/cropsci2016.05.0440
|View full text |Cite
|
Sign up to set email alerts
|

Plant Colorants Interfere with Reflectance‐Based Vegetation Indices

Abstract: Reflectance‐based vegetation indices are commonly used to quantify turfgrass color, estimate chlorophyll content, and make inferences about plant health. These methods are often substituted for visual color ratings, as they are well correlated but more objective. This study examines the utility of reflectance‐based vegetation indices for evaluating turfgrass treated with iron or plant colorants. In a study in Madison, WI, creeping bentgrass (Agrostis stolonifera L.) was treated with ammonium sulfate (2.4 or 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
3
11
1
Order By: Relevance
“…These data are congruent with recommendations by Obear et al. (2017) but further explain specific regions of pigment interference within the far‐red and NIR spectra. Reynolds et al.…”
Section: Discussionsupporting
confidence: 92%
“…These data are congruent with recommendations by Obear et al. (2017) but further explain specific regions of pigment interference within the far‐red and NIR spectra. Reynolds et al.…”
Section: Discussionsupporting
confidence: 92%
“…However, all results were far below the value considered ideal for bermudagrass (445) proposed by Godoy et al (2012). Obear et al (2017) also found no statistical difference in their experiment on the use of colorant, observing values of 221 and 205 in treatments with and without colorant, respectively, which are higher than the results of the present study (Table 2).…”
Section: Resultscontrasting
confidence: 94%
“…With respect to durability of the colorant, only the reflectance index accurately captured the data, where results at 10 days already showing a degradation of the product (Table 2). This result is similar to that described by Obear et al (2017) in an experiment with the use of colorant in bentgrass, where an interval of 14 days was used. However, Braun et al (2016) observed good results in the application of the same colorant used herein on the visual quality of Zosya japonica 'Chisholm'.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although the conversion of raw NDVI values to SI will mitigate many problems that affect reflectance, there are still several problems associated with NDVI that could reduce its effectiveness as a guide for N fertilization. A common practice in turfgrass management is to add a colorant or chelated iron to increase the color quality without additional N. On a creeping bentgrass ( Agrostis stolonifera L.) putting green, NDVI and other reflectance conversions were unable to determine differences in N rates when colorants or iron were applied (Obear et al., 2017). It was concluded that these products reflect light in the red and near‐infrared regions and likely interfere with reflectance‐based vegetation indices that measure canopy reflectance in the same regions of the light spectrum.…”
Section: Discussionmentioning
confidence: 99%